Experiences of Strokes’ Caregiver in Maluku Province: A Qualitative Study - La Rakhmat Wabula; Suahryono Suharyono (Indonesian Journal of Community Health Nursing, 2021)
Introduction:Patients with stroke are dependent on their family to relieve their physical and emotional needs after discharge form the hospital. The family plays an important role in caring for them, which is a stressful task for the caregivers. This study aimed at investigating the experiences of caregivers of patients with stroke.Method: This is qualitative study (descriptive phenomenology), in which the participants included seven caregivers of stroke patients. Data were collected through semi-structured interviews. Data analysis was performed based on Colaizzi.Result: The results in the study were summarized in three main categories: anxiety (tension and stress, concern about economic future), care consequences (fatigue, reduced family interactions), and neglected needs (psychological needs educational needs)Conclusion: According to the purpose of the study and its implications, it is concluded that nurses and physicians should pay more attention to the needs and concerns of patients and their caregivers and try to resolve them with regard to the consequences of the disease.